Transgenerational effects of pyriproxyfen in a field strain of Musca domestica L. (Diptera: Muscidae). - Naeem Iqbal; Nauman Sadiq; Muhammad Nadir Naqqash; Muhammad Usman; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad (PLoS ONE, 2024)
Musca domestica L. (Muscidae: Diptera) is a human and livestock pest especially in tropical and sub-tropical areas. Different insecticides have been used to control this pest that pose serious harmful effects on humans and the environment. The current study was planned to investigate the effects of two concentrations (LC25 and LC50) of pyriproxyfen on biological and population parameters of a field strain of M. domestica. The exposed parents (F0) and their progeny (F1) were studied to examine the transgenerational effects. The results indicated that preadult duration was higher in control (13.68 days) compared to LC50 treated individuals (12.44 days). The male and female longevity was relatively lower in the LC25 treated population i.e. 24.62 and 26.62 days, respectively. The adult pre-oviposition period (APOP) and total pre-oviposition period (TPOP) values were higher in the LC25 treated individuals than those of control. Moreover, oviposition days and fecundity were reduced in the treated individuals as compared to the control treatment. A gradual decrease in the net reproductive rate (R0) was observed (8.46-14.07 per day) while the value of R0 was significantly higher in control. The results suggested that pyriproxyfen can be effectively utilized and incorporated in the management programs of M. domestica.